2021
DOI: 10.1186/s13756-021-00894-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on use, cost and clinical efficacy of automated decontamination devices

Abstract: Background More evidence is emerging on the role of surface decontamination for reducing hospital-acquired infection (HAI). Timely and adequate removal of environmental pathogens leads to measurable clinical benefit in both routine and outbreak situations. Objectives This systematic review aimed to evaluate published studies describing the effect of automated technologies delivering hydrogen peroxide (H202) or ultra-violet (UV) light on HAI rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…The evidence that seemed to support the use of new technologies, such as the peroxide or the UV rays, was recently disproved [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that seemed to support the use of new technologies, such as the peroxide or the UV rays, was recently disproved [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…UVC light falls between 200 and been able to demonstrate reductions in healthcare-associated infections (HAIs) or other infection rates, whereas some systematic reviews have concluded that the evidence is mixed or weak. [13][14][15][16][17][18] Inconsistent results can be attributed in part to the complex nature of infection transmission and other factors such as:…”
Section: Visible Light Spectrummentioning
confidence: 99%
“…However, the daily efforts of healthcare workers and further consistent scientific research are needed to fuel that trend. To minimize the colonization by infectious microorganisms able to persist and thrive in the healthcare environment, new strategies for cleaning and disinfection are being proposed, but with variable success [1][2][3]. Yet, no matter how appealing the new methods and biocide candidates may sound, new insights over already known and extensively used biocides are certainly welcomed and may play a relevant role towards the effective prevention of HAIs.…”
Section: Introductionmentioning
confidence: 99%